Conserved statin-mediated activation of the p38-MAPK pathway protects Caenorhabditis elegans from the cholesterol-independent effects of statins - Irina Langier Goncalves; Sharon Tal; Liza Barki-Harrington; Amir Sapir (Elsevier, 2020)
Objective: Statins are a group of medications that reduce cholesterol synthesis by inhibiting the activity of HMG-CoA reductase, a key enzyme in the mevalonate pathway. The clinical use of statins to lower excess cholesterol levels has revolutionized the cardiovascular field and increased the survival of millions, but some patients have adverse side effects. A growing body of data suggests that some of the beneficial and adverse effects of statins, including their anti-inflammatory, anti-tumorigenic, and myopathic activities, are cholesterol-independent. However, the underlying mechanisms for these effects of statins are not well defined. Methods: Because Caenorhabditis elegans (C. elegans) lacks the cholesterol synthesis branch of the mevalonate pathway, this organism is a powerful system to unveil the cholesterol-independent effects of statins. We used genetic and biochemical approaches in C. elegans and cultured macrophage-derived murine cells to study the cellular response to statins. Results: We found that statins activate a conserved p38-MAPK (p38) cascade and that the protein geranylgeranylation branch of the mevalonate pathway links the effect of statins to the activation of this p38 pathway. We propose that the blockade of geranylgeranylation impairs the function of specific small GTPases we identified as upstream regulators of the p38 pathway. Statin-mediated p38 activation in C. elegans results in the regulation of programs of innate immunity, stress, and metabolism. In agreement with this regulation, knockout of the p38 pathway results in the hypersensitivity of C. elegans to statins. Treating cultured mammalian cells with clinical doses of statins results in the activation of the same p38 pathway, which upregulates the COX-2 protein, a major regulator of innate immunity in mammals. Conclusions: Statins activate an evolutionarily conserved p38 pathway to regulate metabolism and innate immunity. Our results highlight the cytoprotective role of p38 activation under statin treatment in vivo and propose that this activation underlies many of the critical cholesterol-independent effects of statins.